2022
DOI: 10.1021/jacs.2c01380
|View full text |Cite
|
Sign up to set email alerts
|

Desymmetric Partial Reduction of Malonic Esters

Abstract: Desymmetrization of easily available disubstituted malonic esters is a rewarding strategy to access structurally diverse quaternary stereocenters. Particularly, asymmetric reduction of malonic esters would generate a functional group with a lower oxidation state than the remaining ester, thus allowing for more chemoselective derivatization. Here, we report a new set of conditions for the zinccatalyzed desymmetric hydrosilylation of malonic esters that afford aldehydes as the major product. Compared with alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
1
15
1
1
Order By: Relevance
“…More importantly, the dataset revealed a declining stereoselectivity when the equivalent of the organomagnesium increased, presumably due to a transition from a mononuclear to dinuclear complex. Notably, the optimal equal ratio of metal and ligand here contrasts sharply with the dinuclear nature of previous zinc catalysts [13] for malonic esters. It is postulated that when an equal amount of dibutylmagnesium and L8 complex via double deprotonation, one of the three hydroxyl groups would remain and assist the stereocontrol by binding with diketones as a hydrogen bond donor.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…More importantly, the dataset revealed a declining stereoselectivity when the equivalent of the organomagnesium increased, presumably due to a transition from a mononuclear to dinuclear complex. Notably, the optimal equal ratio of metal and ligand here contrasts sharply with the dinuclear nature of previous zinc catalysts [13] for malonic esters. It is postulated that when an equal amount of dibutylmagnesium and L8 complex via double deprotonation, one of the three hydroxyl groups would remain and assist the stereocontrol by binding with diketones as a hydrogen bond donor.…”
contrasting
confidence: 64%
“…As discovered in our previous study of the desymmetric reduction of malonic esters, a family of dinuclear zinc complexes (6) were able to exert excellent enantiocontrol via the coordination with both ester motifs. [13] Here, by harnessing a similar yet distinct chelation mode, a bifunctional catalyst with both a Lewis acidic magnesium center and a hydrogen bond donor (7) are reported to cyanosilylate acyclic 1,3-diketones diastereo-and enantioselectively.…”
mentioning
confidence: 99%
“…Recently, we have accomplished the reductive desymmetrization of all-carbon- 16 , 17 and halogen-substituted 18 malonic esters using a series of dinuclear zinc complexes with a tetradentate ligand. It is envisioned that the inclusion of amino- and oxymalonic esters in this desymmetrization paradigm 19 , 20 would provide an expeditious and diverse synthesis of enantioenriched α-tertiary amines and tertiary alcohols, as these diester substrates ( 4 and 5 ) can be rapidly and modularly prepared from inexpensive amino-, bromo-, and ketomalonic esters ( 1 – 3 ) via facile substitution and addition reactions (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…First, unlike inert alkyl and aryl groups, coordinating and/or acidic nitrogen/oxygen substituents can deactivate the bimetallic catalyst containing both a Lewis acidic and Brønsted basic zinc center 21 . Second, as the enantioselection of the desymmetrization boils down to the size difference between two α-substituents, a pair of carbon substituents of dinstinct sizes (e.g., phenyl vs methyl) were often prerequisite for a highly stereoselective hydrosilylation to quaternary stereocenters 16 , 17 . Comparably, a wide scope of amino- and oxymalonic esters would require catalysts to accommodate heteroatom substituents of diverse shapes and sizes, such as ethers, amides, and alkyl amines, to contrast different carbon sidechains (i.e., small carbon vs large heteroatom substituents and vice versa).…”
Section: Introductionmentioning
confidence: 99%
“…Known compound 8 was subjected to the base-promoted alkylation with homoallylic bromide 9 , which successfully produced 10 in 90% yield. In order to establish the C16 chiral center, desymmetrical monoreduction of the malonate 10 was initially tried, and this approach was proved to be unsuccessful with either a chiral zinc complex/silane or BINOL-coordinated aluminum hydride system. In contrast, we observed that DIBAL-H was capable of reducing only one ester group to aldehyde chemoselectively, although there is no chiral induction in this protocol.…”
mentioning
confidence: 99%